SPATIAL DISTRIBUTION OF ATMOSPHERIC POLLUTION IN DUHOK URBAN AREA BY USING GIS TOOLS - Khaled, Bahzad M.Taher; Dereen JM Albeyboni; Bayan Hazim Ahmed; Ghariba Y. Haji; Sami MA Youssef (Science Journal of University of Zakho, 2023)
Air pollution is becoming a serious challenge in thickly populated areas in the world. The air pollution in Kurdistan region is clearly noticed, especially in areas where pollution sources and human population are concentrated. Urbanization and economic growth are proceeding at a rapid pace, accompanied by increasing emissions of a mixture of greenhouse gases especially from transporting sector, that positively contribute to accelerate climate change around the globe, and also have impacts on public health and vegetation. In order to decrease the effects that caused by atmospheric pollution, suitable monitoring systems are urgently needed that can rapidly and reliably detect and quantify polluting sources and concentration for monitoring by local authorities in order to restrain more damage of the current pollution levels. In this study, GIS with portable gas detector (K-60 IV) KELISAIKE safety equipment, China, have been used to assess the status of NOx, VOCs and noise pollution at 54 randomly selected urban locations of Duhok city. The measurements were taken during the week and weekend days started from 9 am until 4 pm. The results showed that there is a variation in the values of the three variables NOx, VOCs and noise, where the highest values recorded during working days in the locations distributed along the highway and the city center with heavy traffic load and dense human population in comparison to lowest values obtained during weekend days in locations distributed outskirt of the city with lower population and traffic loads. Therefore, likely such connections exist between the urban traffic density and low air pollution quality within urban locations around Duhok city.